Lay Evaluations of Restraints and Prohibitions During the 1st Wave of the COVID-19 Pandemic in Lithuania - Valickas, Gintautas; Švedas, Gintaras; Vanagaitė, Kristina; Barysė, Dovilė (Teisė, 2021)
The article analyzes how, during the 1st wave of the coronavirus pandemic, participants of a study (n = 331) assessed the government-imposed restrictions, prohibitions, liabilities and penalties for non-compliance with said restrictions, and the perceived fairness of the behavior of other people during the pandemic. The article also studies the relationships among these assessments, including the related well-being and sociodemographic characteristics.
Keywords: COVID-19 pandemic; evaluations of applied restraints; responsibility; penalties and perceived justice